The assessment of interleukin-10 and periodontal parameters in chronic kidney disease patients with inflammation of the gum and tooth-supporting tissues following periodontal therapy - Kassim, Nur Karyatee; Abdul Rahman, Nurul Aliya; Hanafi, Muhammad Hafiz; Zainuddin, Siti Lailatul Akmar; Kamarudin, Muhammad Imran; Ahmad, Farizan; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Ibrahim, Hanim Afzan; Wan Ahmad, Wan Muhammad Amir (UPM, 2022)
Introduction: Chronic kidney disease (CKD) is characterized by kidney structure and function abnormalities. CKD also includes permanent nephron loss and a decline in glomerular filtration rate. Most CKD patients have periodon¬titis, a chronic inflammatory disease of the gums and tooth-supporting tissues. Periodontitis is linked to CKD due to the hyper-inflammatory state in both conditions. Interleukin-10 (IL-10) is an inflammatory marker with immuno¬modulatory properties influencing the host’s immune responses. Little is known regarding the effect of periodontal therapy on inflammatory markers and periodontal parameters in CKD patients with periodontitis. Therefore, this study aimed to compare the levels of IL-10 and periodontal parameters before and after receiving periodontal ther¬apy. Methods: Twenty CKD patients with periodontitis (Group 1) and twenty non-CKD patients with periodontitis (Group 2) participated in this study. A blood sample was collected during each visit. Serum IL-10 concentration was analysed using an enzyme-linked immunosorbent assay. The periodontal parameters such as periodontal probing depth, clinical attachment loss, gingival bleeding index and plaque score were also measured. Results: Our findings revealed that IL-10 level was significantly higher (p<0.05) in Group 1 [Mean (SD) = 1.301(0.29)pg/ml] than in Group 2 [Mean (SD)= 0.81(0.27)pg/ml]. Following periodontal therapy, there was a significant reduction (p<0.05) in IL-10 levels and periodontal parameters in both groups. Conclusion: Periodontal therapy has shown improvement in both inflammatory markers and periodontal parameters. IL-10 is a promising inflammatory marker for monitoring the pro¬gression of CKD. Therefore, multicentre and larger sample size studies are needed in the future.